Mapping islamic financial inclusion literature: Trends, key issues, and future research directions - Suhardi Suhardi (Indonesia Accounting Research Journal, 2025)
This study aims to map the development of academic literature on Islamic Financial Inclusion (IFI) from 2020 to 2025 using a bibliometric approach. In the growing need for an inclusive and Shariah-compliant financial system, this study highlights publication trends, author collaboration, contributing institutions, and dominant keywords in the IFI theme. We analyzed the top 15 most-cited articles using VOSviewer software to identify thematic relationships and knowledge networks. The analysis showed that topics such as digital financial inclusion, Islamic microfinance, banking stability, and financial well-being are the primary focus of IFI studies. In addition, there is a dominance of contributions from authors from Southeast Asia, the Middle East, and Africa. The study also found a gap in integrating digital literacy, financial inclusion, and Sharia principles, especially in developing countries such as Indonesia. This research contributes significantly to the intellectual map of IFIs. It serves as a reference for policymakers, academics, and Islamic finance practitioners to develop a more adaptive, equitable, and sustainable financial inclusion strategy under Islamic values.